Social Media Discontinuation: A Systematic Literature Review on Drivers and Inhibitors - Farooq Ali; Dahabiyeh Laila; Maier Christian (Elsevier Ltd., 2022)
Recent practical reports reveal that users leave social media. This behavior is named social media discontinuation (SMD) and is attributed to stress, fatigue, and further negative effects caused while using social media. While current literature points to some causes of SMD, a systematic literature review is needed to identify current research trends, carve out future research directions, and guide practitioners in encouraging users not to close their social media accounts. We thus examine existing research on SMD and identify its drivers and inhibitors. We conducted a systematic literature review by screening 1,270 studies, published in journals and conference proceedings since 2005. We focused on 32 studies that matched our screening guidelines. Our results come up with three SMD drivers and inhibitors categories: individual, relational and platform-specific. Individual drivers and inhibitors can further be divided into cognitive, behavioral, and emotional drivers, whereas platform-specific drivers are related to content and other social media characteristics. Most drivers are from the individual or the relational category. The findings contribute to SMD research by providing a comprehensive state-of-the-art perspective on what drives and inhibits SMD. This lets us develop valuable future research directions, such as the need for future research on SMD inhibitors, which have received little attention. The study further offers valuable practical implications to social media service providers.